AN IMPACT OF SOCIO-ECONOMIC PROCESSES OF THE REGION ON THE ENVIRONMENT - Larisa B. Kalmykova (Статистика и экономика)
An approach to assessment of a stability of socio-economic development of the region with use of elasticity coefficients is given in the article. On the basis of correlation and regression analysis the author constructs the dependence equations between the indicators of the region’s development and environment’s conditions. That makes it possible to evaluate the influence of social and economic processes on the ecosystem of the region.